Estudo da resistência à corrosão em ligas de memória de forma NiTiNb com diferentes teores de Nb - Cronemberger, Maria Eurenice Rocha (Universidade Federal de São Carlos, 2018)
In this work, the corrosion behavior of NiTiNb shape memory alloys (SMA) in aqueous medium containing chloride ions was characterized. The study was performed in alloys of six different compositions, which were melted in an arc-furnace, under controlled atmosphere, with 3, 6 and 9 at.% of Nb addition, while the ration Ni/Ti was maintained constant at 1.00 and 1.07. The objective was to evaluate the Nb content effect on the composition and corrosion resistance of the passive film, supported by its microstructural and thermal characterization. The electrochemical behavior in sodium chloride solution (NaCl) 3.5 w.% was evaluated using potentiodynamic polarization and potentiostatic polarization techniques, to verify the pitting corrosion resistance of alloys, comparing with an equiatomic NiTi alloy. The analyses of the passive film composition was made by X-ray photoelectron spectroscopy (XPS). The alloys exhibit passivity in 3.5% NaCl solution, however, both the passivity zone expansion and the pitting potential (Epite) of the alloys increase their respective magnitudes with the increase of Nb content. On the other hand, the corrosion current density of the alloys are similar, showing that the alloys have the same general corrosion rate, that remains approximately unchanged with composition and microstructure variations. Alloys with Nb contents below 9 at.% exhibit susceptibility to pitting corrosion and cracking corrosion, but they show better resistance compared to binary alloy. The XPS results reveal the formation of a passive film composed mainly titanium and niobium oxides (TiO2 and Nb2O5). The Nb content has a great influence on the pitting corrosion resistance of these alloys due to the incorporation and the enrichment of Nb in the passive film.
Study of corrosion resistance in NiTiNb shape memory alloys with different Nb content
Keywords: Corrosão; NiTiNb; Ligas de memória de forma; Corrosion; NiTiNb; Shape memory alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA